2014
DOI: 10.1038/eye.2013.307
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choroidal thickness evaluation by SD-OCT in adults with obstructive sleep apnea-hypopnea syndrome (OSAS)

Abstract: Objective To assess the macular retina and choroidal thickness change in patients with obstructive sleep apnea-hypopnea syndrome (OSAS) with no significant symptoms and pathological changes in the fundus using spectral domain-optical coherence tomography. Methods This prospective, observational case-control study consisted of 53 eyes of 53 patients with OSAS and 12 eyes of 12 age-matched controls. Macular and choroidal thicknesses were measured by optical coherence tomography. Results The foveal and nasal macu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 30 publications
(35 reference statements)
1
64
0
2
Order By: Relevance
“…This might be due to the origin of the control group that has some suspicious symptoms related with possible sleep disorders, and the small number of subjects. Also, this study revealed a negative correlation between AHI severity and SFCT (28) . However, OSAHS is a risk factor for central serous chorioretinopathy etiology, which has been reported to accompany subfoveal choroidal effusion (7) .…”
Section: Discussionmentioning
confidence: 78%
“…This might be due to the origin of the control group that has some suspicious symptoms related with possible sleep disorders, and the small number of subjects. Also, this study revealed a negative correlation between AHI severity and SFCT (28) . However, OSAHS is a risk factor for central serous chorioretinopathy etiology, which has been reported to accompany subfoveal choroidal effusion (7) .…”
Section: Discussionmentioning
confidence: 78%
“…Tonini et al 13 found similar choroidal blood flow reactivity to CO 2 and O 2 in the OSAS patients and controls in their prospective study, and concluded that ocular microcirculation, which provides adaptive mechanisms, continues long-term in OSAS patients. Contrarily, Xin et al 12 observed significantly lower measurements in severe OSAS patients with regard to the subfoveal and nasal choroidal thicknesses, when compared with the mild-moderate OSAS patients and control subjects. Additionally, Bayhan et al 11 reported significantly thinner choroidal thicknesses 1.5 mm and 3.0 mm nasal to the fovea in severe OSAS patients, when compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The normal function and structure of the choroid is essential for proper retinal function 11,12,14 . The choroid mainly supplies the outer layers of the retina, which contain photoreceptors, and abnormal flow changes may cause photoreceptor death or dysfunction 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We present a case where permanent vision loss was prevented by prompt recognition of the condition seen on fluorescein angiography (FA). To our knowledge, this is the first report of fluorescein angiographic evidence of reversible retinal circulatory abnormalities associated with GCA.…”
Section: Ha Bayhan and S Aslan Bayhanmentioning
confidence: 99%